ANALISIS PENCEMARAN ORGANIK DI PERAIRA¬N PELABUHAN PANGKAL BALAM BERDASARKAN HUBUNGAN KONSENTRASI BOD, COD, DAN TOC DENGAN INDEKS KEANEKARAGAMAN MAKROZOOBENTOS - Intan Tri Aryani; Mohammad Agung Nugraha; Aditya Pamungkas (Scientific Timeline, 2022)
Activities around the waters of Pangkal Balam Harbor can produce organic waste in rivers, estuaries, to the sea which has the potential for negative impact on water quality. Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Organic Carbon (TOC) of sediment are parameters for the amount and organic matter. The purpose of this study was to determine the concentration, criteria, and the pollution status of BOD, COD, and TOC based on the relationship between BOD, COD, and TOC to the macrozoobenthos diversity index (H'). The sampling method was decided based on purposive sampling location with distinct activities. Sampling was carried out in March 2021 in Pangkal Balam Port Waters. BOD analysis using titration method, COD analysis using closed reflux method spectrophotometrically, and TOC sediment using Loss On Ignition method. The results of the study showed that the concentration of BOD ranged from 8.2-12.5 mg/l, COD ranged from 187.23-270.23 mg/l, and sediment TOC ranged from 0.829-18.875%. The relationship between BOD and COD with the diversity index is not significant so that the condition of the waters of Pangkal Balam Port based on the BOD and COD parameters can be said to have not been polluted. Meanwhile, the relationship between the TOC of sediment and the diversity index shows a significant effect so that the status of organic matter pollution based on the TOC is in the polluted status.